In the gaps of the scopic regime (Palíndromo, 2017)
The present article seeks to provoke plausible ruptures in the current of thought proposed by the scopic regime through the study of blindness in the arts, particularly functional blindness and its metaphorical space. Thus, this text puts in evidence authors such as Georges Bataille and Jacques Lacan, and artists such as Luiz Henrique Schwanke – and his works Light Paving Stone (1990) and Light Cube (1991) – and Cildo Meireles with his work Blind Mirror (1970). Finally, the article was basically divided in two parts titled respectively: The Blinding Light: from Bataille to Schwanke and The mirror experience in Lacan and Cildo Meireles. Ultimately, two books were used as a basis for the presented reflection: Downcast eyes: the denigration of vision in twentieth century French thought by Martin Jay and Blindness and Visual Culture: An Eyewitness Account by Georgina Kleege.
Keywords: functional blindness; antiocularcentric thought; Luiz Henrique Schwanke; Cildo Meireles